Regional and sectoral foreign direct investment in Portugal since joining the European union: a dynamic portrait - Melo, I.; Ferreira-Lopes, A.; Monteiro, H. (Review of Urban and Regional Development Studies, 2015)
Despite the very few studies regarding FDI in Portuguese regions - especially regarding its effects - FDI can be an important catalyst for regional economic development and growth. This work studies the existing FDI in the Portuguese regions, analysing its distribution by NUTS III, the sectors in which FDI has more weight in each region, as well as it evolution between 1986 and 2009. Although the relative weight of FDI firms in Portugal remained constant over the years analysed (around 1%), at the same time, these firms spread to all regions of the country, besides the main economic and services agglomerations (Lisboa and Porto). The regions attracted FDI not only for the sectors in which they have already been specialized, but also for other activities, diversifying the regional productive structure of the country. The increase and diversification of FDI coincided with the tertiarization of the economy, being closer to the productive specialization pattern of the country, while continuing to focus mainly on manufacturing.